Vagal Nerve Stimulation Attenuates Ischemia-Reperfusion Induced Retina Dysfunction in Acute Ocular Hypertension - Jiang, Meng-Nan; Zhou, Yu-Yang; Hua, Di-Hao; Yang, Jia-Yi; Hu, Man-Li; Xing, Yi-Qiao (Frontiers in Neuroscience, 2019)
Purpose: The present study aimed to investigate whether cervical vagal nerve stimulation (VNS) could prevent retinal ganglion cell (RGC) loss and retinal dysfunction after ischemia/reperfusion (I/R) injury. Methods: First, rats were randomly divided into sham group (n=4) and VNS group (n=4). Activation of the nodose ganglia(NOG)-nucleus of the solitary tract (NTS)-superior salivatory nucleus(SSN)-pterygopalatine ganglion(PPG) neural circuit was evaluated by c-fos expression after 2 h VNS. Second, rats were randomly assigned to an I/R group (pressure-induced retinal ischemia for 1 h and reperfusion for 1 h in the right eye, n=16) and I/R+VNS group (right cervical VNS for 2 h during the I/R period, n=16). The left eye of each rat served as control. Electroretinogram (ERG), RGC numbers, tumor necrosis factor-α (TNF-α) and vasoactive intestinal polypeptide (VIP) levels in retina were determined. Additionally, the level of VIP in PPG was evaluated. Results: In the first part of the study, compared with the sham group, the VNS group exhibited significantly increased expression of c-fos in NOG, NTS, SSN, and PPG tissues. In the second part of the study, compared with left eyes, retinal function in right eyes (as assessed by the a-wave, b-wave and the oscillatory potential amplitudes of ERG and RGC data) was significantly decreased by I/R. The decreased retinal function was attenuated by VNS. In addition, I/R induced an increase in inflammation, which was reflected by elevated TNF-α expression in the retina. VNS significantly attenuated the increase in I/R-induced inflammation. Moreover, VIP expression in the retina and PPG, which may contribute to the inhibition of the inflammatory response, was significantly increased after VNS. Conclusion: VNS could protect against retinal I/R injury by downregulating TNF-α. Upregulation of VIP expression due to activation of the NOG-NTS-SSN-PPG neural circuit may underlie to the protective effects of VNS.